Temporal defects in photonic topological insulators - Jörg, Christina; Letscher, Fabian; Fleischhauer, Michael; Von Freymann, Georg (2017 Conference on Lasers and Electro-Optics, CLEO 2017 - Proceedings, 2017)
We experimentally study time-dependent defects in a waveguide model of a topological insulator. Backscattering is not observed, but in contrast to static defects, edge modes propagate through the defects.
CRIS-Team Scopus Importer:2023-03-27